IMPLEMENTATION OF READING QUR'ANIC LEARNING (BTQ) (Case study at MAS PAB 4 Klumpang Kebun Hamparan Perak District) - Haidir, Muhammad Azman, Muhammad Riyadh, Rahma Safitri Barus (Journal Analytica Islamica, 2020)
Abstract: This paper aims to determine the form of BTQ learning implementation in MAS PAB 4 Klumpang Hamparan Perak District. The approach used is a qualitative research approach. The results of this study indicate (1) Implementation of BTQ learning in MAS PAB 4 Klumpang Kebun runs quite well. (2) Inhibiting factors in the implementation of BTQ learning in MAS PAB 4 Klumpang Kebun include: the lack of teacher attention to students at the Aliyah level, the educational background of students and economic background. (3) The solutions to overcome these problems are: (a) building cooperation between class teachers and BTQ teachers. (b) BTQ handbook (c) innovation of BTQ learning methods. (d) ongoing evaluationKeywords: Learning, Read Write Al-Qur'an